Factors, outcome, and the solutions of supply chain finance: Review and the future directions - Zericho R. Marak; Deepa Pillai (Journal of Risk and Financial Management, 2019)
In the current highly competitive and fast-changing business environment, in which the optimisation of all resources matters, creating an efficient supply chain is crucial. Earlier studies on supply chains have focussed on aligning product/services and information flows while neglecting the financial aspects. Due to this, in recent times, importance has been given to align financial flows with the other components of the supply chain. The interest in supply chain finance rose after the financial crisis when the bank loans declined considerably, as the need for better management and the optimisation of working capital became obvious. This paper reviews the articles on supply chain finance based on three themes-factors, outcomes, and solutions-while at the same time providing directions for future research on supply chain finance. This article is unique, as it investigates the factors affecting supply chains according to the existing literature. It also sheds light on the outcome of the supply chain without limiting the discussion only to the benefits. Further, it addresses the question: what are the solutions constituting supply chain finance?
Keywords: 330; supply chain management; supply chain finance; working capital; factors; outcomes; solutions; optimisation